Re-Visualizing the Map in Guy Delisle’s Pyongyang - Pedri, Nancy (Arborescences)

(untitled) (Département d'études françaises, Université de Toronto, 2014)
I examine the use of maps in Guy Delisle’s comic Pyongyang. Focusing on the overt manipulation of cartographic techniques, I show how the cartoon map attains accuracy not by hiding, but by accentuating the fictional techniques that went into its making.